The Role of Applying Cybersecurity Standards on Organizational Excellence – A Field Study on Faculty Members at Taibah University in Madinah for the year 2022/ 2023 - Da'as, Rania Mohammad Sameer; Al-Somali, Sabah Abdullah (Journal of Economic, Administrative and Legal Sciences, 2023)
The aim of the study is to identify the role of implementing cybersecurity standards with its dimensions: (Information Security Policy, Information security organization, Human Resources Security, Operations Security) on Organizational Excellence at Taibah University in Madinah in Saudi Arabia. To achieve this aim, the study employed descriptive analytical approach and used a questionnaire as tool to collect data. The study population consisted of all faculty members at Taibah University, and the study sample consisted of (353) faculty members. The most important finding of the study was that the implementation of cybersecurity standards at Taibah University is achieved at very high levels; With an arithmetic mean of (4.78) and a relative weight of (95.6%). Moreover, the study found that organizational excellence is achieved at very high levels, with an arithmetic mean of (4.85), and a relative weight of.  (97%). In addition, the study showed that there is a positive relationship between the implementation of cybersecurity and Organizational Excellence. Eventually, the study recommends that universities in general needs to update their Information Security Policy document periodically to reduce the increasing security risks.
Keywords: Cybersecurity; Information Security Policy; Human Resources Security; Operations Security; Organizational Excellence; Taiba University